Remarks to the World Food Programme Executive Board - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass spoke about how in its first year, the Coronavirus (COVID-19) pandemic is pushing one hundred fifty million people into extreme poverty, ending two decades of steady progress on poverty reduction. Coronavirus (COVID-19) has altered every aspect of commercial activity and trade, shrinking gross domestic products (GDP), fueling a debt crisis and triggering severe food crises. He cautioned about the long-standing problems in the global food system, and how World Food Programme (WFP) and Food and Agriculture Organization (FAO) has estimated that the number of people facing acute food insecurity will double to two hundred sixty-five million people in 2020. He spoke about working along with IMF on effective approaches for debt reduction and debt resolution to address low income countries’ unsustainable debt burdens. He highlighted on establishing a fast-track Coronavirus (COVID) response that has delivered emergency support to one hundred twelve countries so far. He explained that in response to the global food security crisis, the World Bank Group has significantly stepped up investments to strengthen food security in client countries.